A Critique of Expertise for Health Law. Issue 4 (2022) - Ahmed, Aziza
Abstract: A health justice approach requires a progressive critique of expertise. This article considers two recent high-profile cases – the mask mandate and medication abortion -- to understand how we should think the mobilization of expertise in the context of public health law. Following from this, the article offers news ways to better understand how to think of the relationship between health law, expertise, and politics.